2008
DOI: 10.1002/chem.200700727
|View full text |Cite
|
Sign up to set email alerts
|

The Rate‐Determining Step in the Rhodium–Xantphos‐Catalysed Hydroformylation of 1‐Octene

Abstract: The rate-determining step in the hydroformylation of 1-octene, catalysed by the rhodium-Xantphos catalyst system, was determined by using a combination of experimentally determined (1)H/(2)H and (12)C/(13)C kinetic isotope effects and a theoretical approach. From the rates of hydroformylation and deuterioformylation, a small (1)H/(2)H isotope effect of 1.2 was determined for the hydride moiety of the rhodium catalyst. (12)C/(13)C isotope effects of 1.012(1) and 1.012(3) for the alpha-carbon and beta-carbon ato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
59
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 62 publications
8
59
0
Order By: Relevance
“…The observed reaction orders at 363 K suggest that the RDS is either alkene coordination (Reaction 2) or alkene insertion (Reaction 3) into the Rh-H bond. Support for Reaction 3 being the RDS can be drawn from the work of van Leeuwen and coworkers using homogeneous Rh-xantphos complexes [26]. While isotopic experiments ( 1 H/ 2 H and 12 C/ 13 C) were unable to determine the RDS irrefutably, their hybrid quantum mechanical/molecular mechanical (QM/MM) calculations suggested that alkene insertion is the RDS.…”
Section: Rate Expressions For Butanal Synthesismentioning
confidence: 97%
“…The observed reaction orders at 363 K suggest that the RDS is either alkene coordination (Reaction 2) or alkene insertion (Reaction 3) into the Rh-H bond. Support for Reaction 3 being the RDS can be drawn from the work of van Leeuwen and coworkers using homogeneous Rh-xantphos complexes [26]. While isotopic experiments ( 1 H/ 2 H and 12 C/ 13 C) were unable to determine the RDS irrefutably, their hybrid quantum mechanical/molecular mechanical (QM/MM) calculations suggested that alkene insertion is the RDS.…”
Section: Rate Expressions For Butanal Synthesismentioning
confidence: 97%
“…127 For the quantum mechanic part the B3LYP functional was employed along with double-z basis sets. The low level layer treated using the UFF force eld.…”
mentioning
confidence: 99%
“…Such a scenario has been suggested to be occurring in using salicylaldehyde alkene hydroacylation, 22 while the small KIE measured is similar to that proposed for hydride migration step in the hydroformylation of 1-octene. 23 Hofmann and co-workers have demonstrated increased barriers to alkyl migration in related small bite angle systems, 24 consistent with this scenario. Hydride insertion being turnover limiting in this alkyne hydroacylation is in contrast to alkene hydroacylation using aldehyde 1 and small-bite angle diphosphine Rh-catalysts in which fast and reversible hydride insertion is indicated.…”
mentioning
confidence: 75%